SAWAR DARAH OTAK - Yuliana Ulfa, Aluh Sri; Bagus Mahadewa, Tjok Gde (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 The Blood–Brain Barrier (BBB) is a separation of circulating blood from the brain extracellular fluid (BECF) in the central nervous system (CNS). It is a physical barrier between the local blood vessels and most parts of the central nervous system itself, and stops many substances from travelling across it. The BBB is permeable to alcohol, and some heavy metals can cross the blood-brain barrier as well. The concept of the blood brain barrier was first introduced by Paul Ehrlich. He found that intravenous injection of dyes into the bloodstream stained all the tissues in most organs except the brain. Using electron microscopy and electron- dense tracers such as horseradish peroxidase (HRP) a group of scientists demonstrated that the blood- brain barrier is located in endothelial cells of capillaries of the brain.The BBB is to protecting the brain internally as the skull is to protecting it externally. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Blood–Brain Barrier, Central Nervous System